Use of whatsapp messenger and organizational culture towards employee performance at UPTD Puskesmas Purwasari Karawang Regency - Miswan, Miswan; Widaya, Widaya; Rudiana, Deden (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Whatsapp messenger is one of the social media applications in the form of chat that in real time can send messages easily. Good organizational assistance can be reflected in the work culture of the organization, besides that a good organizational culture can also increase motivation for employees at the Purwasari Health Center UPTD which is ultimately expected to improve the quality of its performance in terms of providing Excellent health care to the community. This research aims to analyze the influence of communication by using whatsapp messenger media and organizational culture on the performance of UPTD employees of purwasari Health Center , Karawang Regency, both partially or simultaneously. The method of data collection used is by means of field studies and literature studies with sampling techniques carried out by means of censuses or saturated samples. The number of respondents was 37 respondents who were employees of uptd Puskesmas Purwasari, so the population was a sample. The data in this study was analyzed using SPSS (Statistical Package for The Social Sciences) version 26. The results of the study were obtained: 1). There is a linear relationship between communication built using whatsapp messenger and employee performance and has a positive and significant influence on employee performance. 2) There is a linear relationship between organizational culture and employee performance has a positive and significant influence on karyawan performance. 3) Communication built using whatsapp messenger and organizational culture together has a linear relationship with employee performance and together or simultaneously affects the performance of UPTD employees puskesmas Purwasari Karawang Regency.